DESAIN MEDIA INFORMASI PT. PLN (PERSERO) DISTRIBUSI BANTEN - Maimunah Maimunah; Rifki Adi Syahputra (CCIT Journal, 2018)
The times growing rapidly very possible, for information on access very easily and obtainable by anyone, anytime and anywhere. From this moment the information becomes very important, and with the information makes it easy for people to get the desired data and information is the message in the form of speech or a facial. Information or communication that is perfect it is that can be digested and accepted easily by the public clearly. The Foundation of the current communication tool delivering the message that we know with communication media. Its function is to simplify, accelerate, in conveying information, resulting in more efficient, effective, and concrete. Communication media lately is very useful for the company, because it can help performance and make an example of creativity in the fields of design, such as banners, billboards and banners which is currently enough demand in the workforce. Background problems that exist today in PT. PLN (Persero) distribution of Banten is a lack of media design information update should be therefore made some design information can be addressed to the public and consumers i.e., design the notice regarding the termination of temporary, Info maintenance, banners to commemorate the Christmas day and new year's, design maintenance Info, as users of electricity, electric bayarlah electric smart, timely, applications and mobile money info PLN. With the graphic design of PT. PLN (Persero) distribution of Banten, may be able to attract people's interest in listening or paying attention to the latest information given to PT. PLN (Persero) Distribution Of Banten.